Opportunity to teach and learn standards: colombian teachers’ perspectives (2012)
The aim of this article is to present the outcomes of an exploration of in-service teachers’ perspectives in relation to an opportunity to teach and learn standards in English. A workshop for English teachers from Cali (Colombia) and the neighboring rural sectors was designed and carried out in order to collect the information. Teachers’ perspectives about the topic were explored in terms of three aspects: general considerations that underlie opportunities to learn; standards and conditions in educational institutions (work aspects) and other institutional factors such as human and material resources.Este artículo tiene por objetivo presentar los resultados de una exploración acerca de las reflexiones de un grupo de docentes en ejercicio, respecto a estándares de oportunidad para la enseñanza y aprendizaje del inglés como lengua extranjera. Con este propósito se diseñó y ofreció un taller a profesores de Cali (Colombia) y de la zona rural aledaña. Allí se estudiaron las perspectivas de los docentes en cuanto a tres aspectos: consideraciones generales que subyacen la oportunidad de aprender, estándares y condiciones en las instituciones educativas y otros factores tales como recursos materiales y humanos.